2014
DOI: 10.1155/2014/914326
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Gene Expression ofT-bet,GATA-3,Ror-γt,FoxP3, and Hallmark Cytokines in Chronic Chagas Disease Cardiomyopathy: An Essentially Unopposed TH1-Type Response

Abstract: Background. Chronic Chagas disease cardiomyopathy (CCC), a late consequence of Trypanosoma cruzi infection, is an inflammatory cardiomyopathy with prognosis worse than those of noninflammatory etiology (NIC). Although the T cell-rich myocarditis is known to play a pathogenetic role, the relative contribution of each of the functional T cell subsets has never been thoroughly investigated. We therefore assessed gene expression of cytokines and transcription factors involved in differentiation and effector functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
56
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 49 publications
9
56
0
2
Order By: Relevance
“…The present study demonstrates that classical Th17 cells (CD4 + IL‐17 + IFN‐γ − ) and alternative Th17 (CD4 + IL‐17 + IFN‐γ + ) are found more frequently in CARD2 as compared to IND, with both cells correlating with worse cardiac function. Our results agree with previous studies that demonstrate deleterious effects of IL‐17 in other protozoan diseases and exacerbated pro‐inflammatory environment in Chagas severe heart disease …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present study demonstrates that classical Th17 cells (CD4 + IL‐17 + IFN‐γ − ) and alternative Th17 (CD4 + IL‐17 + IFN‐γ + ) are found more frequently in CARD2 as compared to IND, with both cells correlating with worse cardiac function. Our results agree with previous studies that demonstrate deleterious effects of IL‐17 in other protozoan diseases and exacerbated pro‐inflammatory environment in Chagas severe heart disease …”
Section: Discussionsupporting
confidence: 93%
“…The increased frequency of those cells and its inverse correlation with the cardiac function of chronic patients indicate that they are involved in the immunopathogenesis of the clinical cardiac form of CD. However, although CD4 + CD25 + FoxP3 + and CD4 + CD25 high FoxP3 + cells were more frequent in CARD2, perhaps as an attempt to control exacerbated pro‐inflammatory response, it is possible that, in this group, their suppressive function may be compromised, as severe cardiac patients present increased inflammation in both peripheral blood and cardiac tissue . A previous study demonstrated that CD4 + CD25 high FoxP3 + cells could exert suppressive function in indeterminate patients; additionally, CD4 + CD25 + cells exhibited less suppressive activity in patients with moderate/severe cardiomyopathy .…”
Section: Discussionmentioning
confidence: 96%
“…The inflammatory infiltrate of CCC heart lesions is composed mainly by T cells and macrophages [5,6] and it is considered as typical T-helper 1-mediated disease [7,8] in which mononuclear cells infiltrating CCC heart tissue produce higher amounts of IFN-c, TNF-a and IL-6, with lower levels of IL-2, IL-4 and IL-10 [7,9,10], along with IL-7 and IL-15 [11]. Our group has previously shown the up-regulation of IL-18 expression in CCC heart tissue; moreover, we found a positive correlation between the mRNA expression of IL-18 and both IFN-c and T-bet [12]. In addition, IL-18 along with T. cruzi was able to induce substantial amounts of IFN-c independently of IL-12, it was likely that IL-18 is a mediator of the observed delayed IFN-c production in T. cruzi-infected IL-12p35 À/À mice [13].…”
Section: Introductionsupporting
confidence: 65%
“…Interferon‐γ and tumor necrosis factor‐α are produced in the myocardium of chronically T. cruzi ‐infected hamsters . CCC patients display abundant myocardial production of tumor necrosis factor‐α, interferon‐γ, CCL2/MCP1, and CXCL9/MIG …”
Section: Discussionmentioning
confidence: 99%